Mollaret Meningitis with a High Level of Cytokines in the Cerebrospinal Fluid Successfully Treated by Indomethacin - Kawabori, Masahito (Intern Med, 2018)
A rare case of Mollaret meningitis characterized by four recurrent episodes of aseptic meningitis during a three-year period is reported. The patient showed a high fever and severe headache accompanied by a high level of cerebrospinal fluid (CSF) cytokines, such as interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α). The symptoms and high CSF cytokines were resolved immediately after introducing indomethacin treatment. Reactivation of the latent virus is considered to be the cause of this rare disease, and indomethacin is believed to inhibit the periodic abnormal generation of eicosanoid in the brain, resulting in a reduction in the fever and subsequent inflammation.